Transient Overvoltage Simulation in 500 kV Transmission Line Plan of Sarawak, Malaysia using PSCAD - Yanuar, Z. Arief; Nur Izziani, Roslan; Mohd Hafiez Izzwan, Saad; Lakshmanan, Gurusamy; Nor Asiah, Muhamad (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Transmission system is a crucial system in electrical power since the system transmit the electricity from power generation to consumer load. According to World Bank, the power losses from transmission lines are rapidly increasing from year to year at the rate of 3.85% in the year of 2013 to 5.792%in 2014. Losses in transmission system are most likely from power quality problems such as transients. Transients are the outcome of high unexpected increment in voltage or current surge magnitudes. The peak values of both voltages and current are usuallymore than twice of that normal voltage and current amplitudes. The surges due to transients can vitally cause power system failure and breakdown of electrical equipment especially at the substations. There were few known transient overcurrent and overvoltage problems, which are due to faults, lightning and line energizing, respectively. This research work mainly focuses on simulating transients for 500 kV transmission system which employ Sarawak as the case study location. Sarawak currently has main 275 kVtransmission line covering the whole Sarawak from Miri to Kuching known as Sarawak backbone, but due to lots of industries and rapid development and urbanization boom in Sarawak, there is a planned of 500 kV transmission line as a backup if the 275 kV transmission line proves inadequate. In Sarawak, the 500 kV is planned to be energized at 275 kV. But, in fact this work is for that transmission line to be operated at 500 kV, hence, monitoring the highest transient may occur. The results revealed that lightning and three-phase faults of 1.0 s fault time duration cause the highest change in amplitude of current on the line up to 9.06 pu and 9.27 pu, respectively. The highest lightning amplitude is observed when lightning was simulated at the receiving end of the line which is near to the Tada substation.